Primary intensive care: pilot study of a primary care-based intervention for high-utilizing patients. - Brown, Karen E; Levine, Jeffrey M; Fiellin, David A; O'Connor, Patrick; Sledge, William H (Disease management : DM, 2005)
This pilot study was conducted to determine whether primary care patients with perceived inappropriate high healthcare utilization would require fewer emergency or inpatient services while enrolled in a weekly multidisciplinary clinic. Seventeen high-utilizing or difficult management patients of a primary care center were referred for the special intervention, Primary Intensive Care (PIC). Although not selected for the presence of psychopathology, 16 patients had comorbid psychiatric diagnoses. Patients followed in the PIC Clinic had significantly lower inpatient and emergency department use during their enrollment in the intervention when compared to the matched pre-enrollment time period, although the total hospital cost differences did not reach statistical significance. Patient and staff satisfaction was high, although the intervention was very difficult for the providers.
Keywords: Adult; Aged; Ambulatory Care; Emergency Service, Hospital; Female; Follow-Up Studies; Hospital Costs; Hospitalization; Humans; Male; Middle Aged; Pilot Projects; Primary Health Care; Prospective Studies